A rare case of a benign giant chondroid syringoma of nose - Hage, Neemu; Bakshi, Jaimanti; Rampal, Mayank (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Chondroid syringoma (CS) is a rare benign appendageal tumour of the skin, with histological similarities to pleomorphic adenoma of salivary glands. It typically presents as a slow growing nodular mass generally less than 3 cm, arising from the skin, predominantly in the head and neck region. We report a case of a 61-year-old male with a massive nasal mass attained over a period of 2 years. A fine needle aspiration of the lesion was suggestive of CS. It was excised completely under general anaesthesia. The postoperative histopathology was also consistent with CS. The patient was followed up on a regular basis and was rendered disease free till his last follow up at 4 months. Our purpose of reporting this case is to highlight the rarity of the disease entity, as well as the occasion of it acquiring a large size yet, maintaining its benign nature.